Pengaruh Implementasi Rekam Medis Elektronik dan Pelatihan Terhadap Kinerja Tenaga Kesehatan dengan Motivasi Kerja Sebagai Variabel Intervening di Rumah Sakit Tentara Tingkat II Dustira Cimahi - V. Tjandra, Martinus; Zulfikar, Taufik; Syahidin, Rukhiyat (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Digital transformation has encouraged hospitals to implement Electronic Medical Records (EMR) and training to enhance healthcare workers' performance. This study analyzes the effect of EMR implementation and training on healthcare performance, with work motivation as a mediating variable at RST Tk II Dustira Cimahi. A quantitative survey was conducted with 310 respondents and analyzed using multiple linear regression, t-test, F-test, and Sobel test. Results indicate that EMR has a positive but not significant effect, while training positively and significantly affects both work motivation and performance. Work motivation significantly mediates the effect of EMR and training on performance. The study emphasizes that EMR effectiveness depends on work motivation and continuous training to optimize healthcare workers’ performance.